Supervisory cooperation in Europe from a banking perspective - Van den Spiegel, Freddy (Henry Stewart Talks, 2009)
Financial integration in the EU is a fact, Cross border banks represent an increasing market share, These banks are increasingly organized at a consolidated level, with key functions developed for the whole group at the corporate center level, If supervision is to be effective, it should follow this market reality, The supervisory process should start from the consolidated level and should be fully coherent throughout the group, To achieve this without an institutional revolution, prudential supervision should consist of a college of all involved supervisors with an empowered lead supervisor, chairing this college and with a mediation mechanism at the EU level, in case of disputes between supervisors